Anterior cervical incision‐sparing thyroidectomy: Comparing retroauricular and transoral approaches. Issue 5 (24th September 2018) - Russell, Jonathon O.; Razavi, Christopher R.; Al Khadem, Mai G.; Lopez, Michael; Saraf, Sejal; Prescott, Jason D.; Starmer, Heather M.; Richmon, Jeremy D.; Tufano, Ralph P.
Abstract : Objectives: The robotic retroauricular approach and transoral endoscopic thyroidectomy vestibular approach (TOETVA) have been employed to avoid anterior neck scarring in thyroidectomy with good success. However, outcomes have yet to be compared between techniques. We compare our initial clinical experience with these approaches for thyroid lobectomy at our institution. Methods: A review of initial consecutive patients who underwent robotic facelift thyroidectomy (RFT) (August 2011–August 2016) at our institution was conducted. This was compared with the same number of initial consecutive patients who underwent TOETVA (September 2016–September 2017) at our institution. Demographics, operative time, pathology, complications, and learning curve were compared between cohorts. Learning curve was defined based on the slope of linear regression models of operative time versus case number. Results: There were 20 patients in each cohort. There was no statistically significant difference in demographic data between cohorts. One hundred percent of RFT cases versus 95% TOETVA cases ( P  = .999) were completed without conversion to standard open technique with median operative times of 201 (124–293) minutes versus 188 (89–343) minutes with RFT and TOETVA, respectively ( P  = .36). There was no incidence of permanent recurrent laryngeal nerve injury in either cohort. The slopes of the regression models were 0.29 versus −8.32 ( P  = .005) for RFT and TOETVA, respectively. Conclusion: RFT and TOETVA are safe and feasible options for patients motivated to avoid an anterior neck scar. However, the quicker learning curve without the need for a costly robotic system may make TOETVA the preferred technique for institutions wishing to perform anterior cervical incision‐sparing thyroidectomy. Level of Evidence: 4